28.0k views
0 votes
If T: (x, y) → (x - 3, y + 2), then T -1: (x,y) → _____.

A.(x + 3, y + 2)

B.(x + 3, y - 2)

C.(x/3, -y/2)

D.(3x, -2y)

User Dejah
by
4.8k points

2 Answers

4 votes

the correct answer is b (x+3,y-2)

User Ali Azam
by
4.7k points
4 votes

Answer:

B. (x + 3, y - 2)

Explanation:

Given,


T: (x, y)\rightarrow (x - 3, y + 2),

Let


T^(-1): (x, y)\rightarrow (x+a, y+b)


\implies T^(-1): (x-3, y+2)\rightarrow (x-3+a, y+2+b)

Since,
T^(-1) is inverse of
T

Thus, by the property of inverse function,

x - 3 + a = x ⇒ a = 3

Also, y + 2 + b = y ⇒ b = - 2

By substituting the values,

We get,


T^(-1): (x, y)\rightarrow (x+3, y-2)

Hence, Option B is correct.

User Sunil B
by
5.5k points